A meta-analysis of social media fatigue: drivers and a major consequence - Ou, Mengxue (2023)
Guided by the stressor-strain-outcome framework, this meta-analysis synthesizes 64 empirical studies (N = 28,357) on a list of drivers (i.e., psychological, behavioral, and environmental stressors) and a major consequence (i.e., use discontinuance) of social media fatigue. Results suggest that the behavioral stressor (i.e., SNS addiction) and psychological stressors (i.e., information overload, social overload, system feature overload, and SNS anxiety) demonstrate the largest effects on social media fatigue, whereas environmental stressors (i.e., SNS complexity and SNS usefulness) yield small-to-medium effects. The effect size of social media fatigue on use discontinuance is at a medium-to-large level. Gender, education, social media platform, and sampling method significantly moderate the associations between some stressors and social media fatigue. The meta-analytic structural equation modeling analysis (MASEM) shows that social media fatigue partially mediates the effects of psychological and behavioral stressors on social media use discontinuance. Theoretical and practical implications of this review are discussed.